Results from Germany's 2018 Report Card on Physical Activity for Children and Youth - Demetriou, Yolanda; Hebestreit, Antje; Reimers, Anne Kerstin; Schlund, Annegret; Niessner, Claudia; Schmidt, Steffen C.E.; Finger, Jonas David; Mutz, Michael; Völker, Klaus; Vogt, Lutz; Woll, Alexander; Bucksch, Jens (Journal of physical activity and health, 2018)
Even though positive health effects of regular physical activity (PA) are well known,1,2 national and international surveillance data show that PA is the “pill not taken”. This leads to widespread negative health and economic consequences. The 2018 German Report Card on Physical Activity for Children and Youth provides a comprehensive evaluation of PA levels in different domains and correlated indicators using the Active Healthy Kids Canada (AHKC) grading framework. The Report Card aims to evaluate and benchmark the national PA promotion efforts in children and youth in Germany with the ultimate aim to raise awareness for the promotion of PA. The purpose of this contribution is to summarize the results of the 2018 German Report Card (Figure 1).